Place Management: Social Policy, Government Authority, Community Responsibility - Hendrick, Antonia Suzanne (Curtin University, 2010)
This thesis examines: What is Place Management theory and practice, and how does Place Management inform social policy decisions in Australia? Based in a ‘community of disadvantage’, around ‘childhood development’, and through ‘joined-up governance’, Place Management is based on principles of community development, capacity building, and social capital. A case study of the implementation of the Australian Communities for Children (C4C) programme examines how these principles play out in practice.